Quantitative analysis of phenolic, tannin and flavonoid content and in vitro antifungal activity of wild plant extracts against soil-borne phytopathogenic fungi affecting broccoli - Urdukhe, Yogesh; Mogle, Umesh (Current Botany, 2025)
The present study investigates the phytochemical profiles and antifungal activity of six wild plant species: Solanum nigrum L., Martynia lutea Lindl, Argyreia speciosa (L.f.) Sweet, Barleria cristata L., Acalypha wilkesiana Müll and Vitex trifolia L. The leaves were extracted with ethanol and evaluated for bioactive components, such as phenolics, tannins, alkaloids, flavonoids, and saponins, using qualitative techniques. The total phenolic content (TPC), tannin content (TC), and total flavonoid content (TFC) were quantified using spectrophotometric methods. The antifungal activity of plant extract has been evaluated against soil-borne pathogens, Rhizoctonia solani, Pythium ultimum, Fusarium oxysporum f. sp. conglutinans, and Sclerotinia sclerotiorum using the poisoned food technique at doses ranging from 5% to 20%. Argyreia speciosa demonstrated a significant inhibition of mycelial growth (20%), followed by Acalypha wilkesiana and Vitex trifolia. The synthetic fungicide Bavistin, employed as a control, outperformed the plant extracts. The plant extracts were investigated for their effect on fungal spore germination and enzyme activity, including α-amylase and protease, which are essential to fungal pathogenicity. Treatments with A. speciosa and A. wilkesiana revealed significant suppression of spore germination and enzyme activity, indicating that they have the potential to be effective as fungal biocontrol agents. The findings of this study reveal that the antifungal activity of various plants is affected by their distinct phytochemical profiles, notably their phenolic and flavonoid content. It implies that the plants might be used in sustainable agriculture techniques to control soil-borne plant diseases.